DEVELOPMENT OF MONOCLONAL ANTIBODIES AGAINST MUC1/Y RECOMBINANT PROTEIN EXPRESSED IN E.COLI. - ANUJ KUMAR GUPTA,; PARVINDER KAUR,; HARSHADA PATIL,; UDAYAKUMAR K.,; PARESH B. BHANUSHALI,; MANOJ CHUGH, (International Journal of Pharma and Bio Sciences, 2015)
Cancer antigen 15-3 (CA 15-3) is a MUC1 peptide fragment widely used for the diagnosis of breast cancer. However, because of a lack of sensitivity and specificity, especially during early stages, CA 15-3 alone has not proved to be a reliable marker for early diagnosis of breast cancer. High preoperative concentrations of CA 15-3 are, however, associated with adverse patient outcome. Therefore, an emergent need still exists to find out secondary markers to enhance specificity of serum based detection of breast cancer. MUC1/Y a trans-membrane protein (Non-polymorphic), and a part of MUC1 gene devoid of tandem repeats array and its immediate flanking sequences has also been reported to be expressed in vivo by tumor cells and suggested to be a potential target both for epithelial tumor diagnosis and immunotherapy. In this study, we have expressed and purified recombinant human MUC1/Y from Escherichia coli BL21 (DE3) strain. We could develop a repertoire of monoclonal antibodies, which bound to our recombinant protein. However, most of the antibodies exhibited cross reactivity against normal human serum or His Tag. However, only 9A842G6 specifically reacted to recombinant MUC1/Y protein. 9A842G6 monoclonal antibodies exhibited fluorescence specifically with established breast cancer tissue sections and did not bind to fibroid adenoma sections. Specific reactivity of 9A842G6 mAbs towards MUC1/Y was also confirmed by immunoblotting. Therefore, our observations suggest possible use of MUC1/Y as a potential secondary marker for Breast cancer diagnosis along with CA15-3.